Guest

solve log 5 120 + (x-3) - 2 * log 5 (1-5 (x-3) ) = -log 5 (0.2- 5 (x-4))

solve log5120 + (x-3) - 2 * log5 (1-5(x-3)) = -log5 (0.2- 5(x-4))

Grade:11

1 Answers

Nicho priyatham
625 Points
7 years ago
bring all log terms to 1 side and put (x-3) on other side now 
now add all log terms  using the formulas
  •   mlogab=logabm
  • log a +log b =log(ab)
  • log a-log b =log(a/b)
and REMOVE log on both sides to get the equation
and put 5x-3=a to get the equation
(1-a)2=24a(1-a)
on solving v get a= 1,1/25
so x=3,1
BUT wn we put x=3 in expression we get log50 wh is not define so 
x=1 is oniy solution
PLZ APPROVE IF USEFULL  incase of any doubts drop them in ans box
 

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free